AHNS Series: Do you know your guidelines? AHNS Endocrine Section Consensus Statement: State‐of‐the‐art thyroid surgical recommendations in the era of noninvasive follicular thyroid neoplasm with papillary‐like nuclear features. Issue 9 (26th June 2018) - Ferris, Robert L.; Nikiforov, Yuri; Terris, Davis; Seethala, Raja R.; Ridge, J. Andrew; Angelos, Peter; Duh, Quan‐Yang; Wong, Richard; Sabra, Mona M.; Fagin, James A.; McIver, Bryan; Bernet, Victor J.; et al.
Abstract: The newly introduced pathologic diagnosis of noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP) will result in less bilateral thyroid surgery as well as deescalation in T4 suppressive and radioactive iodine treatment. Although, NIFTP is a nonmalignant lesion that has nuclear features of some papillary malignancies, the challenge for the surgeon is to identify a lesion as possibly NIFTP before the pathologic diagnosis. NIFTP, due to its reduction of overall rates of malignancy, will result in the initial surgical pendulum swinging toward lobectomy instead of initial total thyroidectomy. This American Head and Neck Society endocrine section consensus statement is intended to inform preoperative evaluation to attempt to identify those patients whose final pathology report may ultimately harbor NIFTP and can be offered a conservative surgical plan to assist in cost‐effective, optimal management of patients with NIFTP.